2015
DOI: 10.2337/diaspect.28.4.252
|View full text |Cite
|
Sign up to set email alerts
|

Does Kindness Matter? Diabetes, Depression, and Self-Compassion: A Selective Review and Research Agenda

Abstract: Depression and severe psychological distress are frequently comorbid with diabetes and are associated with reduced adherence to medication and healthy lifestyle regimens, poorer glycemic control, and increased complications. The mixed success of existing treatments for depression in diabetes patients suggests a need for supplementary approaches to this common problem. This article reviews recent evidence for the benefits of self-compassion in chronically ill patients, suggesting its utility as a clinical tool … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 47 publications
(62 reference statements)
2
37
0
Order By: Relevance
“…Together, the three dimensions of self-compassion—self-kindness (versus self-judgement), common humanity (versus isolation), and mindfulness (versus over-identification) (Neff 2003b )—are theorised to bolster the self-regulatory resources necessary for engaging in self-care behaviours, including monitoring and evaluating ongoing behaviour, and emotional regulation (Sirois 2015b ; Terry and Leary 2011 ). For example, self-compassion is proposed to facilitate adaptive emotional responding to the inevitable setbacks that occur when trying to change health behaviours (Sirois et al 2015a ), by promoting self-kind versus self-blaming responses, and mindful acceptance of medical challenges (Brion et al 2014 ; Friis et al 2015a ). Accordingly, self-compassionate people may be less depleted by their medical conditions and thus have more energy to direct towards effective self-regulation of health behaviours (Terry and Leary 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Together, the three dimensions of self-compassion—self-kindness (versus self-judgement), common humanity (versus isolation), and mindfulness (versus over-identification) (Neff 2003b )—are theorised to bolster the self-regulatory resources necessary for engaging in self-care behaviours, including monitoring and evaluating ongoing behaviour, and emotional regulation (Sirois 2015b ; Terry and Leary 2011 ). For example, self-compassion is proposed to facilitate adaptive emotional responding to the inevitable setbacks that occur when trying to change health behaviours (Sirois et al 2015a ), by promoting self-kind versus self-blaming responses, and mindful acceptance of medical challenges (Brion et al 2014 ; Friis et al 2015a ). Accordingly, self-compassionate people may be less depleted by their medical conditions and thus have more energy to direct towards effective self-regulation of health behaviours (Terry and Leary 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Further, as psychosocial research in diabetes gains traction and the field expands, new avenues of investigation have been identified and novel topics of interest have emerged. Examples include stigmatisation of, and discrimination against, people with diabetes,5 48 49 memory and cognition,50 and self-compassion 51. Until now, there is little to no population-based data on these important topics in relation to diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, within diabetic populations, one study has so far 557 demonstrated that Mindful Self-Compassion training can reduce diabetes distress and increase glycemic control amongst people with Type 1 and Type 2 diabetes (Friis,Johnson,Cutfield,& 559 Consedine, 2016). It has also been posited that increased self-compassion could contribute to higher levels of self-care and health-promoting behaviors amongst diabetic individuals (Friis, Consedine, & Johnson, 2015). These findings are important, as evidence suggests that 562 individuals with some chronic illnesses report lower levels of self-compassion and higher levels of shame and self-blame (Harrison et al, 2015;Harrison, Robertson, Goldstein, & Brooks, 2017), but so far interventions have only focused on increasing self-compassion rather than concurrently aiming to reduce perfectionism.…”
Section: Practical Applicationsmentioning
confidence: 99%